METHOD FOR EVALUATING THE EFFECTIVENESS OF TRUNCATED-POSITIONAL CODING FOR INFOCOMMUNICATION SYSTEMS - Barannik, Vladimir; Barannik, Dmitriy; Onyshchenko, Roman; Revva, Kirillo; Babenko, Mykhailo (Science-based technologies, 2024)
The article substantiates the need for further development of science-intensive infocommunication technologies. It is argued that the most important issue is the creation of information support for management processes in the critical sphere of state interests. It is shown that the technologies for providing video information services are influential here. At the same time, mobile technological means are used to obtain video information resources, taking into account the requirements for the efficiency and reliability of information. However, such complexes have certain resource limitations, including in relation to: transmission rate, energy potential, management efficiency. On the other hand, there are certain requirements for the quality of video information resources. Their completeness and integrity are understood here. Accordingly, the requirements for the characteristics of on-board infocommunication technologies are increasing. Hence, contradictions arise regarding the requirements and capabilities of on-board infocommunication technologies in the systems of providing video information services for the processes of managing the critical sphere of the state. The direction of solving the scientific and applied problem is substantiated. It refers to the use of technologies for encoding video information resources. For the development of coding technologies, it is proposed to use alternative approaches. This is due to the need for an additional increase in the amount of redundancy that is eliminated in the compression process, while reducing its dependence on the mechanisms of psychovisual coding. One of these areas is the development and use of truncated positional coding technologies in the process of reducing the redundancy of transformed video segments. At the same time, it is necessary to create a methodology for evaluating the effectiveness of the created approaches to encoding video information resources. An informative model has been developed for estimating the bit volume, which measures the amount (volume) of information in the diagonals of the transformant based on taking into account the features of its combinatorial configuration according to its non-uniformly diagonal format by truncated-positional coding.